Compact numerical modelling of transient condensate layer formation on small components during vapour phase soldering. (June 2022) - Bozsóki, István; Illés, Balázs; Géczy, Attila
Abstract: In this paper transient condensation and heat transfer been investigated on a printed circuit board (PCB) and a surface mounted (SMD) capacitor during a vapour phase reflow soldering (VPS) process. Classic VPS processes provide rapid heating with high heat transfer coefficient rates due to condensation that forms a continuous liquid film on the surfaces. Our aim was to develop a simple and fast computable method that, instead of relying on static descriptions, can reproduce the transient dynamics of the process. It was defined as an inverse heat conduction problem (IHCP) and proposed a solution based on finite difference modelling (FDM) with an alternating direction implicit (ADI) scheme. The layer dynamic was described with a parametric differential equation, and it was coupled to the concentrated and distributed thermal models of the PCB and the capacitor. The parameter values were determined by fitting to measured data. It was found that the heat transfer coefficient is inversely proportional to the layer thickness, and it changes over time according to the dynamic properties of layer growth. It was corroborated that the heat transfer depends on the geometry and thermal properties of the heated surfaces in VPS ovens. The presented method shows good agreement with the validation data. The new method provides a significant update over previous modelling approaches describing the condensation-based heating of the VPS process.